Improper Diving Behavior Affects Physiological Responses of Acropora hyacinthus and Porites cylindrica - Zhang, Yu; Huang, Jianzhong; Li, Xinke; Song, Cuiping; Xia, Jingquan; Ren, Yuxiao; Wang, Aimin; Li, Xiubao (Frontiers in Marine Science, 2021)
Human activities beyond ecosystem capacity have resulted in serious effects on corals worldwide. Nowadays, many studies have focused on the influence of diving activities on coral communities, while the knowledge of physiological changes under corresponding environmental stresses remains largely undetermined. In the study, we aimed to investigate the physiological effects of touching, ammonia nitrogen enrichment (5 μmol•L-1), and sediment cover (particle size of less than 0.3 mm), which simulated improper self-contained underwater breathing apparatus (SCUBA) diving behaviors, on Acropora hyacinthus and Porites cylindrica in Wuzhizhou Island, the South China Sea. For A. hyacinthus, continuous touching caused the tentacles to shrink and secrete mucus, which consumed energy and dissolved oxygen. The bone growth rate was 96% lower compared with the control group. There was a rapid decline of Fv/Fm and alpha under the dual impacts of high ammonia nitrogen and touching, while the Chl a concentration and tissue biomass were decreased by 36% and 28% compared with touching alone, respectively. Nevertheless, corals increased zooxanthellae density to relieve the effects from a lower concentration of Chl a under a high nutrient environment. Constant touching and sediment cover in diving areas with elevated ammonia content affected the photosynthesis and respiration of corals, and a significant decrease was observed for energy reserves, zooxanthellae density, and Chl a concentration. Coral bleaching occurred on day 7. For P. cylindrica, the decreasing magnitude of Fv/Fm and alpha under different stresses in the subsequent phase was less compared with A. hyacinthus. The contents of carbohydrate and protein under continuous touching were decreased by 7% and 15% compared with the control group, respectively, causing the negative growth. Under the dual influences of high ammonia nitrogen